Application of Box-Behnken design for optimization of formulation parameters for nanostructured lipid carriers of candesartan cilexetil - Thakkar, Hetal P.; Desai, Jagruti L.; Parmar, Mayur P. (Asian Journal of Pharmaceutics (AJP), 2014)
This study deals with development and optimization of nanostructured lipid carriers (NLCs) of candesartan cilexetil (CC) for improving its oral bioavailability. From solubility and lipid‑water partition studies of CC in various lipids, glyceryl monostearate (GMS) and glyceryl monocaprylate were selected as solid lipid and liquid lipid, respectively. NLCs were formulated by hot melt‑emulsification‑ultrasonication method. A three‑factor, three‑level Box–Behnken design was used to optimize the independent variables, lipid: drug ratio (X1), solid lipid: liquid lipid ratio (X2) and surfactant concentration (X3). Different batches were prepared and evaluated for responses, particle size (Y1), zeta potential (Y2) and % entrapment efficiency (Y3). Response surface plots and perturbation plots were constructed to study the effect of factors on responses. The optimized formulation containing X1 - 22.47:1, X2 - 7.23:1 and X3 - 1.97% was prepared and evaluated. Observed values for Y1, Y2, and Y3 were found to be closer to the predicted values thus validating the optimization method. Differential scanning calorimetry thermograms of pure drug, GMS and lyophilized drug loaded NLCs indicated complete miscibility of drug into lipids. The release of CC from the NLCs conducted in artificial gastric fluid (pH 1.2) was much higher than in phosphate buffer solution (pH 6.8). The formulated NLCs were found to be more stable at refrigerated condition (5°C ± 3°C) as compared with room temperature (25°C ± 2°C/60% RH% ± 5% RH). The use of design approach helped to identify critical formulation parameters in CC loaded NLCs preparation. Key words: Candesartan, hypertension, nanostructured lipid carriers, oral bioavailability partition study